A Systematic Review Uncovering Modifiable Influences on Statin Adherence - Rosenberg J; Lampridou S; Moores A; Garfield S; Wingfield D; Judah G (Patient Preference and Adherence)
Javiera Rosenberg,1 Smaragda Lampridou,1,2 Amelia Moores,1 Sara Garfield,3 David Wingfield,1,4 Gaby Judah1 1Department of Surgery & Cancer, Imperial College London, London, UK; 2Imperial College Healthcare NHS Trust, St. Mary’s Hospital, London, UK; 3School of Pharmacy, University College London, London, UK; 4Hammersmith and Fulham Partnership, North End Medical Centre, London, UKCorrespondence: Javiera Rosenberg, Department of Surgery & Cancer, Imperial College London, St Mary’s Hospital, Praed Street, London, UK, W2 1NY, Email j.rosenberg22@imperial.ac.ukAbstract: Statins are effective in reducing cardiovascular disease (CVD) risk, but adherence rates remain low globally. Understanding and addressing modifiable influences on adherence is key to improving outcomes. Existing reviews have methodological limitations, often failing to integrate qualitative and quantitative data or consider specific barriers to statin adherence. This systematic review aimed to identify modifiable barriers and facilitators to statin adherence using the Theoretical Domains Framework (TDF). A comprehensive search of Embase, MEDLINE, PsycINFO, and CINAHL was conducted, covering studies from January 1998 to November 2023. Data were coded to TDF domains and synthesized to identify specific influences on adherence. The nature of the evidence (qualitative or quantitative) was recorded for each influence, and variations among patient groups were noted. Seventy studies from 20 countries were included, with only one focused on ethnic minorities. The most commonly identified domains affecting adherence were “Beliefs about Consequences”, “Knowledge”, ‘Environmental Context and Resources’, and “Social Influences”. Key factors included knowledge of disease, perceived disease threat, perceived benefits of statins, and patient-provider communication and trust. While side effects had inconsistent associations with adherence, forgetfulness was mainly addressed in quantitative studies, and social influences were highlighted in qualitative research. This review identified modifiable factors that could improve statin adherence. Future research should focus on addressing barriers faced by underrepresented groups to create more inclusive and effective interventions that enhance patient support and communication for better health outcomes.Plain language summary: People are prescribed statins to prevent strokes and heart attacks. This study combines findings from previous studies to understand why many people do not take statins as prescribed.Common barriers to taking statins included not thinking being at risk of strokes and heart attacks, believing statins are harmful, experiencing side effects and poor communication and trust with healthcare professionals.Common things encouraging statin taking included thinking statins have benefits, having cholesterol levels checked, routines and methods to remember statin intake and having ways of dealing with side effects. Keywords: medication adherence, psychological determinants, dyslipidaemia, theoretical domains framework